1981
DOI: 10.1073/pnas.78.7.4485
|View full text |Cite
|
Sign up to set email alerts
|

Specific transcriptional initiation in vitro on murine type C retrovirus promoters.

Abstract: We have investigated the ability of molecularly cloned murine type C retroviral DNA to direct accurate initiation of RNA synthesis when added to cell-free extracts. Two different cloned proviruses were used. The first was derived from an integrated molecule of AKR murine leukemia virus and contains adjacent host information. The origin of the second was an unintegrated permuted copy of Harvey murine sarcoma virus. We found that the leukemia virus cloned provirus, as predicted by structural considerations, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…This would place the 5' end of a putative RNA polymerase III transcript around position 45 to 47 (Fig. 2), a location consistent with published data (15). We still cannot assess the physiological significance of this sequence in determining transcripts within the Ha-MuSV genome in vivo.…”
supporting
confidence: 67%
“…This would place the 5' end of a putative RNA polymerase III transcript around position 45 to 47 (Fig. 2), a location consistent with published data (15). We still cannot assess the physiological significance of this sequence in determining transcripts within the Ha-MuSV genome in vivo.…”
supporting
confidence: 67%
“…Region 3 consists of about 65 bp between region 2 and the CCAAT box, and region 4 consists of 100 bp at the extreme 3' end of U3 that contains the viral promoter ( Fig. 1) (28,56). We determined the base that appears most frequently at each position in the alignment ( Fig.…”
Section: Ccaatmentioning
confidence: 99%
“…Recent studies have shown that LTRs contain bidirectional promoters that are able to initiate transcription in both the sense and antisense orientations (2)(3)(4). With respect to expression of viral genes, a promoter within the 5= LTR of the provirus regulates sense transcription and, therefore, production of the viral gene products necessary for viral particle synthesis (gag, pro, pol, and env) as well as regulatory and accessory genes (5). For all human T-cell leukemia virus (HTLV) family members (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), as well as for the human immunodeficiency virus type 1 (HIV-1) (16-18), a separate promoter or promoters within the 3= LTR regulate antisense transcription.…”
mentioning
confidence: 99%